Freshwater biodiversity conservation through source water protection: Quantifying the potential and addressing the challenges. Issue 7 (3rd June 2019) - Abell, Robin; Vigerstol, Kari; Higgins, Jonathan; Kang, Shiteng; Karres, Nathan; Lehner, Bernhard; Sridhar, Aparna; Chapin, Emily
Abstract: Water insecurity is a defining feature of the Anthropocene, with degraded water quality and unreliable flows putting the well‐being of upstream and downstream communities, both human and aquatic, at risk. Within this context, the protection of drinking water at its source – 'source water protection' – is growing as a complementary water security solution to conventional built infrastructure, particularly but not only to address non‐point source pollution. An assessment of the likely source catchments of 4000 cities, supplying water to as many as 1.7 billion city dwellers, found that 85% of the total area of the catchments overlaps with freshwater ecoregions of high biodiversity value. Source water protection could contribute to conserving important freshwater biodiversity elements in these catchments, through activities such as land protection, restoration, and agricultural and ranching best‐management practices. Empirical evidence supporting the benefits of these types of activities to freshwater species and ecosystems is sparse, especially when considered at the scales required to achieve meaningful conservation objectives. This article explores the potential of source water protection to deliver freshwater conservation benefits, and solutions are proposed to address the challenges related to evidence gaps, trade‐offs, and financing. The broader opportunity for leveraging water security investments for biodiversity conservation, and the overall efficiencies that may accrue from optimizing for multiple benefits simultaneously, are discussed in the context of global frameworks such as the Sustainable Development Goals.